A non-transit fully compliant tristable mechanism capable of direct switching between every two stable positions. (15th April 2022) - Li, Lingling; Li, Bo; Chen, Guimin
Abstract: A tristable compliant mechanism is a mechanical device that can hold three distinct positions where the strain energy stored in the flexible members falls in its minima. This unique feature makes them very useful in many applications such as overload protection, threshold acceleration sensing, and shape reconfiguration. For the currently available tristable designs, there is a middle stable position among the three stable positions, and switching between the other two stable positions requires to pass through the middle one. This work presents a novel fully compliant tristable mechanism called non-transit tristable mechanism (NTTM), which can directly switch between every two stable positions without passing through the other one. A kinetostatic model using the chained beam-constraint-model is developed for the proposed mechanism, based on which two NTTMs are successfully identified. The non-transit tristable behaviors of the NTTM designs are verified by the results of nonlinear finite element model and the experimental results of a 3D printed prototype. Highlights: A NTTM that can directly switch between every two stable positions is proposed. A kinetostatic model using CBCM is developed. NTTMs designs are successfully identified. Non-transit tristable behaviors are verified by NFEA model and experimental results.